Kualitas Hidup Peserta Prolanis Diabetes Melitus Tipe II: A Systematic Review - Feby Febriany Feby Febriany (BPJS Kesehatan, 2023)
Indonesia is facing a triple burden of diseases, where non-communicable diseases experience an increase in incidence every year, one of which is Diabetes Mellitus. One program for preventive measures and further complications is prolanis as a form of improving the quality of life of diabetes mellitus type 2 sufferers. The aim of this research is to see a picture of the quality of life of prolanis participants, especially diabetes mellitus type 2. Articles were searched using the GARUDA and Google Scholar databases. The flow of the systematic review method used PRISMA which ultimately resulted in 10 articles relevant to the research. The results showed that the majority of prolanis diabetes mellitus type 2 participants had a moderate quality of life, which was influenced by several factors such as prolanis club activity, environmental support, and adherence to taking medication.